An Analysis of the Properties of a Newly Proposed Non‑Randomised Response Technique - Kowalczyk, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
Non‑randomised response (NRR) techniques are modern and constantly evolving methods intended for dealing with sensitive topics in surveys, such as tax evasion, black market, corruption etc. The paper introduces a new NRR technique that can be seen as a generalisation of the well‑known crosswise model (CM). In the paper, methodology of the new generalised crosswise model (GCM) is presented and the maximum likelihood estimator of the unknown population sensitive proportion is obtained. Also, the problem of privacy protection is discussed. The properties of the newly proposed GCM are examined. Then the GCM is compared with the traditional CM. The paper shows that mathematically the CM is a special case of the newly proposed generalised CM and that this generalisation has high practical relevance.